2014
DOI: 10.1002/cphc.201402449
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of Self‐Assembled Porphyrin Networks at a Solid/Liquid Interface: Local Manipulation under Global Control

Abstract: Molecules of (5,10,15,20-tetraundecylporphyrinato)-copper(II) [(TUP)Cu] can self-assemble into four different polymorphs at the interface between highly oriented pyrolytic graphite and 1-octanoic acid. Scanning tunneling microscopy (STM) reveals that it is possible to combine the global control over monolayer structure, provided by the composition and concentration of the supernatant solution, with local control, from nanomanipulation by the STM tip. In the initially formed monolayer, with a polymorph composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…These kinetically locked structures differed in molecular density, a parameter that could be controlled by the concentration of CuTUP in the supernatant solution at the moment of layer deposition. When a nanoshaving procedure was carried out on a CuTUP polymorph domain with certain density, underneath a supernatant solution with a concentration that would encode a polymorph of either a lower or a higher density, the domain that was shaved away was subsequently refilled with molecules from the liquid that would self‐assemble into predominantly the polymorph structure with that particular density . A similar nanoshaving procedure of a CuTUP layer under a supernatant containing a different TUP derivative (i.e., CoTUP ) resulted in the subsequent local insertion of those molecules in a surrounding domain of CuTUP molecules (Figure ).…”
Section: Externally Applied Manipulation Of Molecular Assembliesmentioning
confidence: 99%
“…These kinetically locked structures differed in molecular density, a parameter that could be controlled by the concentration of CuTUP in the supernatant solution at the moment of layer deposition. When a nanoshaving procedure was carried out on a CuTUP polymorph domain with certain density, underneath a supernatant solution with a concentration that would encode a polymorph of either a lower or a higher density, the domain that was shaved away was subsequently refilled with molecules from the liquid that would self‐assemble into predominantly the polymorph structure with that particular density . A similar nanoshaving procedure of a CuTUP layer under a supernatant containing a different TUP derivative (i.e., CoTUP ) resulted in the subsequent local insertion of those molecules in a surrounding domain of CuTUP molecules (Figure ).…”
Section: Externally Applied Manipulation Of Molecular Assembliesmentioning
confidence: 99%
“…In previous work, we had constructed a variety of supramolecular assemblies of (metal-) porphyrins at solid–liquid interfaces and imaged their spatial organization with the help of liquid-STM [7]. By applying specific molecular design, we were able to precisely control the two-dimensional (2D) polymorphic behavior of these assemblies by varying the nature or the concentration of the solution in the STM experiments [22,23,24]. We also constructed 2D assemblies of catalytically active Mn(III) porphyrins and investigated their reactivity with oxygen and the epoxidation of alkenes at the single-molecule scale [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…in the presence of molecular building blocks, has emerged as a most powerful tool to create and characterize confined 2D assemblies. [23][24][25][26][27][28] In this approach a sacrificial blocking layer is locally shaved off by the probe, and molecules suspended in solution can adsorb and assemble on the exposed surface area. Previous in situ STM nanoshaving studies on graphite, both by our group and other groups, have shown a preferential molecular adsorption orientation inside the exposed surface area.…”
Section: Introductionmentioning
confidence: 99%